Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1093/ajcn/61.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of abdominal and visceral fat with computed tomography and dual-energy x-ray absorptiometry

Abstract: These studies were undertaken to compare dual-energy x-ray absorptiometry (DXA) and computed tomography (CT) measurements of abdominal fat and to determine whether anthropometry could be combined with DXA to predict intraabdominal (visceral) fat mass in humans. Twenty-one volunteers underwent abdominal CT scans, DXA, and anthropometry. DXA- and CT-measured total abdominal fat were similar (8448 +/- 5005 and 8066 +/- 5354 mL, respectively; NS) and were highly correlated (r = 0.985, P < 0.001). The combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
246
1
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(258 citation statements)
references
References 14 publications
4
246
1
6
Order By: Relevance
“…As opposed to Jensen et al (1995), we found a difference in the attenuation value between the subcutaneous and intraabdominal fat. This might be explained by continual technical developments that have resulted not only in improved spatial resolution (2566256 pixel image matrix vs 5126512), but also in markedly improved grey-scale resolution.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…As opposed to Jensen et al (1995), we found a difference in the attenuation value between the subcutaneous and intraabdominal fat. This might be explained by continual technical developments that have resulted not only in improved spatial resolution (2566256 pixel image matrix vs 5126512), but also in markedly improved grey-scale resolution.…”
Section: Discussioncontrasting
confidence: 80%
“…However, by assuming a constant mineral to lean tissue relation, fat estimates in patients with reduced bone mineral is overestimated (van der Kooy & Seidell, 1993). DEXA also does not permit calculations of compartmental fat distribution (Jensen et al, 1995) because it is a simple projection technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each volunteer was positioned with his/her arms sufficiently separated from the trunk to allow the creation of a region of interest that included only truncal contents. Abdominal fat measured by this method has shown a strong correlation with computed tomography-measured abdominal adipose tissue (Jensen et al, 1995). Physical characteristics of the subjects are presented in Table 1.…”
Section: Subjectsmentioning
confidence: 89%
“…Whole body and regional fat mass and fat-free mass were assessed by dual energy X-ray absorptiometry (DXA) (model DPX-MD; Lunar, Madison, WI, USA) using software version 4.6 and the 15-min scan time. This computerised analysis was also employed to measure abdominal fat (Jensen et al, 1995). Specifically, abdominal fat was assessed by manually drawing a region of interest on the abdomen using the top of the diaphragm as the cephalad limit and the top of the femur (greater trochanter) as the caudal limit.…”
Section: Subjectsmentioning
confidence: 99%